Increasing diversity of land planarians (Platyhelminthes: Geoplanidae) in the Interior Atlantic Forest with the description of two new species and new records from Argentina - Negrete, Lisandro; Brusa, Francisco (Zootaxa, 2017)
Here, we describe two new species of land planarians of the genera Pasipha and Imbira from the Atlantic Forest of Argentina: Pasipha quirogai sp. nov. and Imbira negrita sp. nov. Their external features and internal anatomy distinguish them from their congeners. Pasipha quirogai sp. nov. is about 40mm long, characterized by brown beige dorsal pigmentation with a golden yellow median band and thin graphite black para-median stripes, cylindrical pharynx, extrabulbar prostatic vesicle with paired proximal portion, male atrium with small folds in its proximal part, and female canal opening into the dorso-caudal wall of the female atrium. Imbira negrita sp. nov. is about 110mm long, with jet black dorsal pigmentation, pharynx collar-type, short female canal opening in the postero-dorsal portion of the female atrium, and epithelial lining of female atrium with stratified appearance. We also provide exhaustive descriptions of Geoplana quagga, Obama ladislavii, and Paraba multicolor, all recorded for the first time in Argentina, by analysing anatomical features of taxonomic relevance. In addition, we improve the description of G. quagga, mainly regarding the musculature, secretory cells, and the copulatory apparatus.